Implementation Of Tik-Tok Learning Media in Pugung Raharjo Local History Perpectiv Era 4.0 - Dwi Gesti Jayanti; Zulkarnain Zulkarnain (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
This study aims to determine the implementation of Tik-Tok-based learning in the perspective of Pugung Raharjo's local history era 4.0. The research uses descriptive qualitative research methods with a case study approach. Data collection techniques with the following steps: (1) observation, (2) in-depth interviews, (3) documentation. The results obtained are: (1) Learning Media Concepts, (2) Tik-Tok-Based Learning, (3 Local History of Pugung Raharjo Archaeological Sites, (4) Components of Skill Values in History Learning, (5) Implementation of Tik-Tok-Based Learning in Pugung Raharjo Local History Learning. The results show that the innovation of Tik-Tok-based application learning media can be used by teachers as millennial learning media in the era of the industrial revolution 4.0. The advantages of the Tik-Tok-based learning media developed include, 1) attracting interest student learning, 2) train students in language and speaking, 3) express creativity and 3) boost student motivation in learning